Persuasão em charges multimodais: humor e ironia com apoio da relação metáfora/metonímia:um enfoque da linguística sistêmico-funciona - Casagrande, Daniela Costa da Silva (2021)
Contemporary multimodal media communication is used everywhere, by almost all speakers, and yet remains opaque in terms of its social effects. What to think about text and the meaning of it arising in a world in which multimodal semiotic entities begin to dominate the communication scenario? The socio-semotic perspective of language, when using the socio-prefix, does not incorporate it by a simple change of nomenclature, but takes a position by pointing out the notion of partner for the social system, that is, for culture. The meaning of culture is considered as a set of semiotic system, a set of meanings that interrelate. Thus, whenever we consider multimodal or complex sets of signs, we may ask: which mode carries greater functional weight compared to others? How does each mode contribute to the meaning being built? How are semiotic resources made available to sign producers and by whom? The objective of this doctoral thesis is the analysis of multimodal cartoons, examining the persuasive function of humor and irony from the point of eye of metaphor and metonymy, with the support of Systemic-Functional Linguistics. The cartoon is a pictorial representation of a caricature not only of events, but also of personalities, focusing on political, historical and social facts, of a controversial or not nature, which circulate daily in national and international media. Conceptual metaphor always involves a degree of perspective, when certain traits are highlighted while others remain obscured; conceptual metonymy thanks to its indicial character is a cognitive process that evokes a frame, allowing the addressed to infer the implicit content of the message through verbalvisual cues, with the support of their cultural knowledge and the immediate context of communication The analysis of the cartoons is based on the conceptual relationship between metaphor and metonymy, since metaphors necessarily need underlying metonymizations. The research shows that the cartoons perform persuasion via the union between humor and irony, recounting for so much the metonymic frame instigated by the lexical choices made by the author of the text, allowing the reader, in his interaction with the cartoon, to recover the conceptual metaphor, goal of persuasion